2020
DOI: 10.1080/09515070.2019.1570081
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to a special section on practice-based research and counselling psychology

Abstract: To introduce this special section about practice-based research and counselling psychology, I first provide a brief overview of the discourses and methods of practice-based research in counselling psychology and psychotherapy fields. I then discuss each of the three papers appearing in this special section, before concluding with some further reflections on the questions and issues raised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…An analysis by the authors of field research published in the New Zealand Journal of Counselling over the last 20 years found that, with very few exceptions, the approach involved thematic analyses of interviews, focus groups, diaries and personal stories. Qualitative research would seem to have a good fit with what Henton (2020) suggested were the perceptions counsellors have of the emotional complexity and subjectivity of their work. There is a caveat: qualitative research is an umbrella for ‘a vibrant and contested field’ (Brinkmann et al., 2014, p. 17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An analysis by the authors of field research published in the New Zealand Journal of Counselling over the last 20 years found that, with very few exceptions, the approach involved thematic analyses of interviews, focus groups, diaries and personal stories. Qualitative research would seem to have a good fit with what Henton (2020) suggested were the perceptions counsellors have of the emotional complexity and subjectivity of their work. There is a caveat: qualitative research is an umbrella for ‘a vibrant and contested field’ (Brinkmann et al., 2014, p. 17).…”
Section: Discussionmentioning
confidence: 99%
“…It is not a given that counsellors will regard assessment of their counselling as worthwhile. Many may regard it as at odds with their understanding of the emotional complexity and inherent subjectivity of the counselling relationship (Henton, 2020). The challenge for any practice‐based research counsellor is to find an assessment of process and outcomes that is compatible with their counselling, has high face validity for the client and has proven sensitivity to shifts in the client's well‐being.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations